TATA BANGUNAN PADA JALAN DI.PANJAITAN DAN JALAN ALI MAKSUM DI YOGYAKARTA - Sanitha, Onie Dian (Universitas Atma Jaya Yogyakarta, 2014)
Abstract: Building composition is tightly related with functions and activities of users, so it should be able to give expression and information through elements of building. The corridor ofÂ DI. Panjaitan and Ali Maksumâ€™s street has a historical value as special image of the city in Yogyakarta. The purpose of this research is to identify and evaluate the condition of building through the comparison the results through identification with rules of government regulation. Data will obtained through field observations and evaluated in accordance with Government direction to know detail the extent to which a building can be setup to follow government directives and the extent of D.I. Panjaitan and Ali Maksumâ€™s street are capable of expressing the meaning of a historical road that traversed with imaginary axis.Keywords: Identification, evaluation, comparison, building composition, the expressionAbstraksi: Tata bangunan erat kaitannya dengan fungsi dan kegiatan pengguna, sehingga mampu memberi ekspresi dan informasi melalui elemen-elemen sebuah bangunan. Koridor Jalan D.I. Panjaitan dan Ali Maksum di Yogyakarta memiliki nilai historis sebagai pembentuk citra istimewa Kota Yogyakarta. Tujuan penelitian ini adalah mengidentifikasi dan mengevaluasi kondisi tata bangunan melalui perbandingan hasil identifikasi dengan aturan regulasi pemerintah. Data diperoleh melalui pengamatan lapangan dan dievaluasi sesuai dengan detail arahan pemerintah untuk mengetahui sejauh mana penataan bangunan dapat mengikuti arahan pemerintah dan sejauh mana koridor Jalan D.I. Panjaitan dan Ali Maksum mampu mengekspresikan makna historis sebuah jalan yang dilalui sumbu imajiner Yogyakarta.Kata Kunci: Identifikasi, evaluasi, perbandingan, tata bangunan, ekspresi